Physical Losses in Bagged Paddy Grain in Open Environment - Thakur, A K; Gupta, A K (Journal of Agricultural Engineering, 2008)
A study was conducted on the exchange of moisture by paddy grain stored in sacks of jute, woven polypropylene and canvas in the open air. Grain moisture and temperature followed a simiiar pattern of variation to ambient relative humidity and temperature. Moisture was aggravated to around 20% by the effect of rain in all sacks. Once the moisture increased in woven polypropylene sack, the fabric imparted resistance to the release of moisture from paddy to the environment and, therefore, more damage occurred. The jute sack showed good exchange of moisture between the paddy and the environment and vice-versa; as a result, less damage occurred. The vapour transmission from canvas was higher than the jute but, in practice canvas obstructed air movement to some extent through the sack and similarly decreased moisture transfer from the paddy to the environment. The physical loss of paddy as a comprehensive effect of moisture, temperature, relative humidity and duration of storage was assessed by visual examination and found to be 16.7, 35.2 and 30.3% in jute, woven polypropylene and canvas sacks respectively at the end of twelve month storage. These losses were compared with the loss in rice processing yield and the difference was found significant at the end of six months, however, insignificant after twelve months. Overall the jute sack demonstrated good storage ability of paddy grain even where it was fully exposed to open environment.